2022-RA-1631-ESGO ABC of surgical teaching: time to consider a global blueprint for holistic education. (20th October 2022) - Sideris, Michail; Emin, Elif Iliria; Hanrahan, John Gerrard; Odejinmi, Funlayo; Mallick, Rebecca; Nicolaides, Marios; Velmahos, George; Athanasiou, Thanos; Papalois, Vassilios; Papalois, Apostolos
Abstract : Introduction/Background: Educating and equipping students and trainees into clinicians capable of meeting healthcare demands and service provision needs is essential. Unprecedented events like COVID-19 pandemic, highlight urgent need for reformation of training to ensure high quality education is maintained. To this end, we describe an innovative and globally adaptable blueprint for establishing a surgical curriculum, aiming to optimize preparation of future surgeons Methodology: We used a structured protocol to synthesize evidence from previous systematic reviews focused on surgical education alongside a series of focused original educational studies. This approach allowed incorporation of prospectively applied novel ideas into the existing landscape of published evidence. All material used for this proof of concept derives from the outputs of a dedicated research network for surgical education (eMERG). Results: We propose the foundation blueprint framework called 'Omnigon iG4' as a globally applicable model. It allows adaptation to individual local educational environments for designing, appraising and/or refining surgical curricula. We also describe the 'Omnigon iG4 Hexagon Pragmatic Model, ' a novel perspective model which assesses the performance of our blueprint in a multi-layer fashion. This 'Hexagon' model is the first to introduce pragmatic outcomes in curricula performance assessment. Conclusion: This proof of concept, 'Omnigon iG4, ' proposes an adaptable version of a curriculum blueprint. The framework allows educators to establish a surgical curriculum with the ability to map out competencies, permitting full control over their intended learning outcomes. This can form the basis for developing globally adaptable multifaceted Simulation-Based learning (SBL) courses or even surgical curricula for undergraduates.